Quantitative determination of spin–orbit-induced magnetic field in GaMnAs by field-scan planar Hall measurements - Seongjoon Park (Nature Portfolio, 2021)
Abstract Spin–orbit-induced (SOI) effective magnetic field in GaMnAs film with in-plane magnetic anisotropy has been investigated by planar Hall effect measurements. The presence of SOI field was identified by a shift between planar Hall resistance (PHR) hystereses observed with positive and negative currents. The difference of switching fields occurring between the two current polarities, which is determined by the strength of the SOI field, is shown to depend on the external field direction. In this paper we have developed a method for obtaining the magnitude of the SOI fields based on magnetic free energy that includes the effects of magnetic anisotropy and the SOI field. Using this approach, the SOI field for a given current density was accurately obtained by fitting to the observed dependence of the switching fields on the applied field directions. Values of the SOI field obtained with field scan PHR measurements give results that are consistent with those obtained by analyzing the angular dependence of PHR, indicating the reliability of the field scan PHR method for quantifying the SOI-field in GaMnAs films. The magnitude of the SOI field systematically increases with increasing current density, demonstrating the usefulness of SOI fields for manipulation of magnetization by current in GaMnAs films.